Weather shocks and child nutritional status in rural Bangladesh: Does labor allocation have a role to play? - Homma, Kirara; Islam, Abu Hayat Md. Saiful; Matsuura-Kannari, Masanori; Debela, Bethelhem Legesse (Elsevier Ltd., 2025)
Despite efforts to improve food and nutrient intake in the last decades, child undernutrition remains a challenge, particularly in rural areas of developing countries. Although household labor reallocation after weather shocks is an important ex-post strategy to mitigate weather-shock impacts, a comprehensive understanding of how households adjust their labor and its implications in the context of child health is lacking. We investigate how different forms of labor activity is associated with the impacts of rainfall shock on child nutritional status, using nationally representative panel data from rural households in Bangladesh, in conjunction with monthly precipitation and temperature data for the last three decades. We find that less rainfall during the main cropping season in the previous year worsens nutritional status of children under the age of five years, while less rainfall in the current year increases child nutrition. We also find heterogeneous associations of different types of labor with the identified linkages between rainfall shock and child nutritional status. While maternal off-farm selfemployment plays a potential role in mitigating the negative impact of rainfall shortage, maternal on-farm labor may worsen child nutrition under rainfall shocks. We do not find any significant associations for household-level total labor time and other household members’ labor time. Our results therefore underscore the importance of providing sufficient off-farm employment opportunities for mothers and addressing maternal time constraints through targeted policies to cope with extreme weather and improve child nutrition.